Sustainability assessment of the Piracicaba Capivari and Jundiaí 2020-2035 River Basin Management Plan: analysis of water availability and demand indicators (Gestão & Regionalidade, 2021)
Water, a central natural resource for human life, is heterogeneously distributed on the planet. Regarding the river basins of the Piracicaba, Jundiaí and Capivari rivers, the concern with meeting the needs of the population in a permanent and sustainable way and improvements in the conditions of the water balance has given rise to actions by the regulatory Agencies. The objective of the work is to analyze the indicators of water availability and demands of the PCJ Basins, aiming to point out how the evaluation model of the sustainability principles proposed by Gibson can be adopted in order to guarantee the basins' sustainability. The adopted methodology is of qualitative, descriptive, and exploratory nature with documentary technical procedure. It is concluded that Gibson's sustainability assessment model can contribute to monitor the evolution of the goals of the indicators regarding the spatialization of demands and the water balance.
Keywords: Sustainability assessment; PCJ basins; Sustainability Indicators; Water availability; Water demands